Ethnic fractionalization, migration and growth - Dana Schüler; Julian Weisbrod (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2006)
This paper has the aim of contributing to the existing research by analyzing two particular topics. First of all, we update the data set used by Alesina et al.(2003) into the 1990s to analyze the robustness of their results in a wider time range. Furthermore, we analyze whether the effect of ethnic fractionalization is the same in different regions, particularly focusing on Sub-Saharan Africa and Latin America. Secondly, we empirically investigate, if ethnic fractionalization might be positive in a nation which is ethnically diverse due to immigration. We try to distinguish between these two different kinds of ethnic fractionalization in order to determine if the result empirically indicates this multidimensionality of the index of ethnic fractionalization.
Keywords: 330